Mechanisms and treatment of femoropoplitealin-stent restenosis - Kareem, A K; Fakhri, O M; Ismail, A E; Taib, Ishkrizat; Nemah, Mohammed Najeh (The Mattingley Publishing Co., Inc., 2019)
The problem of stent restenosis (SRI) in the femoropopliteal artery (FP) has not yet been resolved; the predictive factors of the mechanisms and treatment in FP-ISR are unclear. The objective of this study is to investigate and give a clear explanation of the mechanisms and factors of FP-ISR that contributed to ISR, as well as a brief survey of the methods that have been used to treat FP-ISR. Methods of treatment with FP-ISR, such as medical, endovascular and bypass surgery, are used for several types of FP-ISR, the DEB device chosen as the first recommended method due to its effectiveness and ease of use.